Development of Islamic Educational Institutions in Brunei Darussalam: Challenges and Prospects - Vegia Oviensy; Dede Rosyada; Muhammad Zalnur; Binti Salleh, Nur Fatihah Wahidah (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
This article discusses the development of Islamic educational institutions in Brunei Darussalam in the social, political, and cultural context of the country. As a country that adheres to an Islamic monarchy system, Brunei Darussalam makes Islamic education an integral part of the national education system. This study aims to examine the dynamics of the growth of Islamic educational institutions, from basic education to higher education, and the government policies that support it. On the other hand, this article also highlights the various challenges faced, such as globalization, the development of information technology, and the need for competent teaching staff. Nevertheless, the prospects for Islamic education in Brunei remain bright along with the government's strong commitment to making this country a Zikir State based on Islamic values. This study uses a qualitative-descriptive approach with an analysis of official documents, academic literature, and data policies. The results of the study indicate that the success of the development of Islamic education in Brunei is highly dependent on the ability of educational institutions to adapt to changing times without abandoning the principles of Islamic law.